Socioeconomic Profile of Lymphadenitis Tuberculosis Patients in The Outpatient Department of dr. Soetomo Hospital, Surabaya, Indonesia - Ghifari, Adiarsya; Sahudi; Dewanti, Linda (Journal of Community Medicine and Public Health Research, 2025)
Tuberculosis (TB) remains one of the most lethal infectious diseases worldwide, with a rising incidence of lymphadenitis TB, the most common form of extrapulmonary TB (EPTB) in recent years. Lymphadenitis TB can be transmitted through primary infection via the oropharyngeal mucosa, and various socioeconomic factors may influence the risk of infection. Understanding the socioeconomic profile and risk factors associated with lymphadenitis TB is crucial for effective control and prevention strategies. This descriptive cross-sectional study aims to investigate the socioeconomic profile of lymphadenitis TB patients and analyze potential risk factors. Sampling was conducted using a total sampling method, including medical records and interviews via Google Forms or WhatsApp. The sample comprised all lymphadenitis TB outpatients at the General Hospital dr. Soetomo, Surabaya, from January to December 2022, resulting in 180 eligible patients, 103 of whom agreed to the interview. Among the 180 patients, the majority were female (56%), aged 11-20 years (24%), and high school graduates (41%). Among 103 interview participants, most had a monthly income below the minimum wage (55%). Most respondents preferred to cook their meals (62%), with a significant proportion having an income below the average salary (62%). Most respondents (76%) showed good awareness of lymphadenitis TB signs, but nonspecific and mild symptoms led to delayed treatment-seeking in 39% of patients. These findings suggest a potential association between various socioeconomic profiles and lymphadenitis TB infection, although further research is needed to strengthen this association.